Comparative Study on Anti-Inflammatory Activity and Phytochemical Constituents of Essential Oil, Steamed and Non-Steamed Extracts of Zingiber Ottensii Valeton - Muanrit, Patcharaporn; Panthong, Sumalee; Poomirat, Saovapak; Saesiw, Ubonwan; Sakpakdeejaroen, Intouch (Trends in Sciences, 2026)
The rhizome of Zingiber ottensii Valeton (ZT) has traditionally been used to treat wounds and various digestive disorders, including flatulence, stomachache, and peptic ulcers, as well as to alleviate inflammatory conditions. However, the impact of the steaming process - commonly employed in Thai folk medicine to prepare ZT rhizomes - on their anti-inflammatory activity and chemical constituents has not yet been scientifically investigated. Therefore, this study aimed to compare the anti-inflammatory activities, analyze the chemical composition, and quantify bioactive constituents of essential oil, including steamed and non-steamed extracts. In vitro anti-inflammatory activities were assessed by measuring NO inhibition using Griess reagent in RAW 264.7 cells, as well as IL-6, TNF-α and PGE2 production using an ELISA test kit. Chemical composition was analyzed using GC/MS, and bioactive constituents in the extracts were quantified by HPLC. Among all ZT extracts, the essential oil (ZTEO) exhibited the strongest inhibitory effect on NO and IL-6 production. In comparison, the non-steamed hexane (ZTNH) and ethanol (ZTNE) extracts were significantly more effective than the steamed hexane (ZTSH) and ethanol (ZTSE) extracts in suppressing these inflammatory mediators. Zerumbone also demonstrated remarkable efficacy in inhibiting NO and IL-6, being at least 57-fold more potent than diclofenac. GC-MS analysis revealed notable differences in the chemical profiles of steamed and non-steamed ZT extracts and essential oil. Zerumbone and α-humulene were identified as the major sesquiterpenes in all tested samples, while terpinen-4-ol was absent in both the steamed hexane and ethanol extracts. The HPLC results further confirmed a significant decrease in zerumbone content in the steamed extracts compared to their non-steamed counterparts. Overall, the steaming process appeared to reduce both the anti-inflammatory activity and zerumbone content of Zingiber ottensii rhizomes, suggesting that non-steamed rhizomes are preferable for preserving their bioactive compounds and therapeutic potential. HIGHLIGHTS The essential oil, hexane and ethanol extracts of Zingiber ottensii Valeton (ZT) rhizome exhibited potent anti-inflammatory properties, primarily through the inhibition of key pro-inflammatory mediators, NO and IL-6. The non-steamed ZT extracts were significantly more effective than the steamed extracts in suppressing NO and IL-6 inflammatory mediators. Zerumbone and α-humulene were found to be the main monocyclic sesquiterpene constituents in ZT essential oil, as well as in hexane and ethanol extracts. Zerumbone demonstrated remarkable efficacy in inhibiting both NO and IL-6 productions, being at least 57-fold more potent than diclofenac. Steaming was found to reduce both the biological activity and zerumbone content of ZT extracts compared to their non-steamed counterpart. GRAPHICAL ABSTRACT